Imaging of Cellular Oxidoreductase Activity Suggests Mixotrophic Metabolisms in Thiomargarita spp - Jake V. Bailey (American Society for Microbiology, 2017)
ABSTRACT The largest known bacteria, Thiomargarita spp., have yet to be isolated in pure culture, but their large size allows for individual cells to be monitored in time course experiments or to be individually sorted for omics-based investigations. Here we investigated the metabolism of individual cells of Thiomargarita spp. by using a novel application of a tetrazolium-based dye that measures oxidoreductase activity. When coupled with microscopy, staining of the cells with a tetrazolium-formazan dye allows metabolic responses in Thiomargarita spp. to be to be tracked in the absence of observable cell division. Additionally, the metabolic activity of Thiomargarita sp. cells can be differentiated from the metabolism of other microbes in specimens that contain adherent bacteria. The results of our redox dye-based assay suggest that Thiomargarita is the most metabolically versatile under anoxic conditions, where it appears to express cellular oxidoreductase activity in response to the electron donors succinate, acetate, citrate, formate, thiosulfate, H2, and H2S. Under hypoxic conditions, formazan staining results suggest the metabolism of succinate and likely acetate, citrate, and H2S. Cells incubated under oxic conditions showed the weakest formazan staining response, and then only to H2S, citrate, and perhaps succinate. These results provide experimental validation of recent genomic studies of Candidatus Thiomargarita nelsonii that suggest metabolic plasticity and mixotrophic metabolism. The cellular oxidoreductase response of bacteria attached to the exterior of Thiomargarita also supports the possibility of trophic interactions between these largest of known bacteria and attached epibionts. IMPORTANCE The metabolic potential of many microorganisms that cannot be grown in the laboratory is known only from genomic data. Genomes of Thiomargarita spp. suggest that these largest of known bacteria are mixotrophs, combining lithotrophic metabolism with organic carbon degradation. Our use of a redox-sensitive tetrazolium dye to query the metabolism of these bacteria provides an independent line of evidence that corroborates the apparent metabolic plasticity of Thiomargarita observed in recently produced genomes. Finding new cultivation-independent means of testing genomic results is critical to testing genome-derived hypotheses on the metabolic potentials of uncultivated microorganisms.